Peran Deteksi Tumbuh Kembang Anak dalam Stimulasi - Dhiva Shahilla Saragih; Nur Hairani Siregar; Nur Zakiyah; Rizka Hasanah Nst; Khadijah Khadijah; Homsani Nasution (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2026)
Child growth and development detection is a comprehensive screening process that aims to identify early potential problems or developmental delays in early childhood. Through standardized detection instruments, health workers and educators can monitor the achievement of child development milestones in various domains, including motor, language, cognitive, and social-emotional. When detection results indicate irregularities, early intervention in the form of personalized stimulation becomes crucial. Effective stimulation is based on a deep understanding of the child's individual needs and is designed to stimulate areas of development that are delayed. Longitudinal research shows that children who receive early stimulation interventions after growth and development problems are detected show significant improvements in adaptive abilities, social interactions, and academic achievement later in life. Therefore, the integration of child growth and development detection into the health service system and early childhood education is an important investment to create a healthy, intelligent, and competitive generation. In addition, collaboration between parents, teachers, and health workers is needed so that the monitoring and stimulation process can take place consistently, directed, and sustainable to support the optimization of children's growth and development.